Pandemic Flu Planning in the Community: What Can Clinical Ethicists Bring to the Public Health Table? - Berlinger, Nancy (Cambridge quarterly of healthcare ethics, 2008)
It is still remarkably difficult for public health officials charged with developing and implementing pandemic influenza preparedness plans at the community level—where care is delivered—to obtain clear, concrete, and consistent guidance on how to construct plans that are both ethical and actionable. As of mid-2007, most of the federal and state pandemic plans filed with the Centers for Disease Control and Prevention, describing how public health officials will coordinate public agencies and private entities in the event of an outbreak, failed to include ethical guidance for first responders responsible for providing essential services and making fair decisions during a public health emergency.